PENINGKATAN HASIL BELAJAR SMASH BOLAVOLI MELALUI PEMBELAJARAN BERBASIS MEDIA - Arisman STKIP Pamane Talino Ngabang (Jurnal MensSana, 2019)
This study aims to improve student learning outcomes in learning volleyball smash through media-based learning. The method used is action research design Kemmis and Taggart. The subjects in this study were students of SMA Santo Tomas X totaling 38 people.Research in cycle 1 meeting performed 3 times, starting from initial tests to measure students' abilities before the given action. After the act of learning undertaken, researchers gave a final test on the students and the result is a complete student as many as 16 students with a percentage of completeness 42.11%, when compared to the success criteria specified actions, namely 80% of the study conducted in cycle 1 could not be said to be successful , The study was continued to cycle 2 with slight changes and additions to the previous learning of each action and the second cycle will be implemented as much as 3 meeting. The final test in cycle 2 showed excellent improvement as many as 32 students get finished with a percentage of 84.21%. In other words, this study also no longer need to be continued because it is in accordance with the criteria of success of 80%.Based on these results we can conclude that: 1) through media-based learning can improve student learning outcomes in learning smash volleyball, 2) the application of media-based learning gives students the convenience and can motivate students in implementing the learning.